FROM TRADITION TO COMPREHENSION: LEVERAGING THE WISDOM OF 'KENTONGAN' IN DISCOVERY LEARNING TO FOSTER SCIENTIFIC LITERACY - Septiana, Adela; Tyas, Rizki Arumning (Jurnal Pendidikan Matematika dan IPA, 2025)
Scientific literacy is essential for equipping students to solve real-world problems and engage meaningfully with scientific concepts. However, Indonesian students continue to exhibit low performance in international assessments, including PISA and TIMSS. This study aims to examine the effectiveness of the discovery learning model enriched with the local wisdom of kentongan"”a traditional wooden instrument used in community communication"”to enhance students"™ scientific literacy in the topic of vibrations, waves, and sound. This research uses a quasi-experimental design involving 62 eighth-grade students from a public junior high school in Indramayu, divided, divided into control and experimental groups The instruments used include pretest and posttest questions as well as observation sheets, while data analysis was conducted through Independent Sample T-test and effect size. The intervention used student worksheets and teaching modules that linked physics concepts with the cultural function of kentongan. Results showed a significant difference in scientific literacy outcomes between the groups, with the experimental group demonstrating higher normalized gain scores across three key aspects: explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data. The effect size was very high (Cohen"™s d = 2.41), confirming the strong impact of the model. The findings suggest that integrating local culture into discovery-based learning can create more meaningful and contextual science education, fostering students"™ engagement and scientific understanding.